Ratio Legis Pembatasan Kedudukan Hukum bagi Pembentuk Undang-Undang dalam Pengujian Undang-Undang - Fence Wantu; Novendri Mohamad Nggilu; Suwitno Imran; Rahmat Teguh Santoso Gobel (The Constitutional Court of the Republic of Indonesia, 2022)
The discourse on limiting the legislators standing to submit a constitutional review is not an entirely new issue to analyze. However, these things still need to be examined to explore the legal ratio of limitation of the legislator’s standing to submit a constitutional review by the Constitutional Court. This research specifically answers the questions: (a) how are the dynamics of the use of the legislators standing in the constitutional review? (b) what is the legal ratio for limiting legislators standing in the constitutional review? This study uses a normative legal research method by analyzing secondary data in the form of legislation, the Constitutional Court decisions, and literature related to legislators standing to submit the constitutional review. The results of this study indicate that the legal ratio limiting legislators’ standing can be traced through the legal considerations of the Constitutional Court decisions from 2003-2019.